Common Core Genes Play Vital Roles in Gastric Cancer With Different Stages - Yu, Zhiyuan; Liang, Chen; Tu, Huaiyu; Qiu, Shuzhong; Dong, Xiaoyu; Zhang, Yonghui; Ma, Chao; Li, Peiyu (Frontiers in Genetics, 2022)
Background: Owing to complex molecular mechanisms in gastric cancer (GC) oncogenesis and progression, existing biomarkers and therapeutic targets could not significantly improve diagnosis and prognosis. This study aims to identify the key genes and signaling pathways related to GC oncogenesis and progression using bioinformatics and meta-analysis method. Methods: Eligible microarray datasets were downloaded and integrated using meta-analysis method. According to tumor stage, GC gene chips were classified to three groups. Subsequently, three groups’ differentially expressed genes (DEGs) were identified by comparing gene data of tumor group with matched normal specimens, respectively. Enrichment analysis were conducted based on common DEGs among three groups. Then PPI networks were constructed to identify relevant hub genes and sub-networks. The effects of significant DEGs and hub genes were verified and explored in other datasets. Additionally, the analysis of mutated genes was also constructed using gene data from TCGA database. Results: After integration of six microarray datasets, 1229 common DEGs consisted of 1065 up-regulated genes and 164 down-regulated genes were identified. COL1A2, TIMP1, THY1 and BGN were selected as significant DEGs throughout GC development. The low expression of GHRL was associated with high lymph node ratio (LNR) and poor survival outcome. Subsequently, we constructed PPI network of all identified DEGs, and gained 39 sub-networks and top 20 hub genes. Enrichment analysis were performed for common DEGs, the most related sub-network, and top 20 hub genes. We also selected 61 metabolic DEGs to construct PPI networks and acquired relevant hub genes. CEP55 and POLR1A were identified as hub genes associated with survival outcome. Conclusion: The DEGs, hub genes, enrichment analysis for GC with different stages were comprehensively investigated, which contribute to explore the new biomarkers and therapeutic targets.